The brain structure and function abnormalities of migraineurs: A systematic review and neuroimaging meta-analysis - Chen, Zhu-Hong; Cui, Yu-Ling; Sun, Jing-Ting; Li, Yu-Ting; Zhang, Chi; Zhang, Yang-Ming; Li, Ze-Yang; Shang, Yu-Xuan; Ni, Min-Hua; Hu, Bo; Yan, Lin-Feng; Wang, Wen (Frontiers in Neurology, 2022)
Objectives To quantitatively summarize the specific changes in brain structure and function in migraine patients. Methods A literature screening of migraine was conducted from inception to Sept 1, 2022, in PubMed, Web of Science, Cochrane Library, and Medline databases using the keyword combination of “migraine and MRI”. Activation likelihood estimation (ALE) was performed to assess the differentiation of functional connectivity (FC), regional homogeneity (ReHo), and grey matter volume (GMV) of migraine patients. Results Eleven voxel-based morphometry (VBM) studies and 25 resting-state fMRI (rs-fMRI) studies (16 FC and 9 ReHo studies) were included in this study. ALE analysis revealed the ReHo increase in the brainstem and left thalamus, with no decreased area. Neither increased nor decreased regions were detected in FC and GMV of migraine patients. Conclusions The left thalamus and brainstem were the significantly activated regions of migraine. It is a meaningful insights into the pathophysiology of migraine. The consistent alterated brain areas of morphometrical and functional in migraine patients were far from reached based on current studies.